Regeneration of the digestive tract of an anterior-eviscerating sea cucumber, Eupentacta quinquesemita, and the involvement of mesenchymal–epithelial transition in digestive tube formation - Akari Okada; Mariko Kondo (Zoological Letters, 2019)
Abstract Sea cucumbers (a class of echinoderms) exhibit a high capacity for regeneration, such that, following ejection of inner organs in a process called evisceration, the lost organs regenerate. There are two ways by which evisceration occurs in sea cucmber species: from the mouth (anterior) or the anus (posterior). Intriguingly, regenerating tissues are formed at both the anterior and posterior regions and extend toward the opposite ends, and merge to form a complete digestive tract. From the posterior side, the digestive tube regenerates extending a continuous tube from the cloaca, which remains at evisceration. In posteriorly-eviscerating species, the esophagus remains in the body, and a new tube regenerates continuously from it. However, in anterior-eviscerating species, no tubular tissue remains in the anterior region, raising the question of how the new digestive tube forms in the anterior regenerate. We addressed this question by detailed histological observations of the regenerating anterior digestive tract in a small sea cucumber, Eupentacta quinquesemita (“ishiko” in Japanese) after induced-evisceration. We found that an initial rudiment consisting of mesenchymal cells is formed along the edge of the anterior mesentery from the anterior end, and then, among the mesenchymal cells, multiple clusters of epithelial-like cells appears simultaneously and repeatedly in the extending region by mesenchymal–epithelial transition (MET) as visulalized using toluidine blue staining. Subsequently, multiple cavities were formed surrounded with these epithelial cells, and appeared to coalesce with each other to form into multiple lumens, and to eventually become a single tube. This anterior tube then fused to the tube regenerated from the posterior rudiment. Thus, we elucidated the process of regeneration of the anterior portion of the gut in an anteriorly eviscerating species, and suggest the involvement of MET and fusion of cavities/lumens in regeneration of the digestive tube.